Speech Intelligibility and Subjective Evaluation of Music Playback of Sound Transducers with Glass and Wooden Membrane - Wersényi, Gy. (Acta Technica Jaurinensis, 2014)
Novel state-of-the-art designer loudspeaker solutions offer “invisible audio” applications by applying a relatively small transducer onto glass or wooden plates, surfaces such as windows, tables, doors etc. Although manufacturers promise high quality transmission and good technical parameters, reliable measurement data do not exist. In our former evaluation, the SolidDrive system with glass membrane of different shapes, sizes, fixation methods was analyzed using vibration analysis, acoustic measurements and numerical simulations in COMSOL/FEM. This paper presents experimental results of standardized speech intelligibility measurements as well as subjective evaluation of the system.